2010
DOI: 10.1159/000318043
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Arm Phase II Trial of First-Line Paclitaxel in Combination with Lapatinib in HER2-Overexpressing Metastatic Breast Cancer

Abstract: Introduction: Lapatinib, an orally active tyrosine kinase inhibitor of epidermal growth factor receptor ErbB1 (EGFR) and ErbB2 (HER2), has activity as monotherapy and in combination with chemotherapy in HER2-overexpressing metastatic breast cancer (MBC). Methods: This phase II single-arm trial assessed the safety and efficacy of first-line lapatinib in combination with paclitaxel in previously untreated patients with HER2-overexpressing MBC. The primary endpoint was the overall response rate (ORR). Secondary e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 37 publications
3
27
0
1
Order By: Relevance
“…In the clinical setting, the combination of lapatinib and capecitabine is indicated for the treatment of patients with advanced HER2-postive (HER2+) breast cancer in progression after treatment with chemotherapy plus trastuzumab [9]. Combined with paclitaxel, lapatinib is active as first-line treatment [10]. Unfortunately, some patients are constitutively resistant to lapatinib treatment and, even in responders, the disease often progresses because of the selection of tumor cells that have acquired resistance to the drug [11].…”
Section: Introductionmentioning
confidence: 99%
“…In the clinical setting, the combination of lapatinib and capecitabine is indicated for the treatment of patients with advanced HER2-postive (HER2+) breast cancer in progression after treatment with chemotherapy plus trastuzumab [9]. Combined with paclitaxel, lapatinib is active as first-line treatment [10]. Unfortunately, some patients are constitutively resistant to lapatinib treatment and, even in responders, the disease often progresses because of the selection of tumor cells that have acquired resistance to the drug [11].…”
Section: Introductionmentioning
confidence: 99%
“…Lapatinib is an orally active dual TKI that has been used in combination with capecitabine or letrozole for the treatments of patients with advanced breast cancer (25). We previously reported that lapatinib inhibited the function of ABCB1, ABCG2 and MRP10 (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…22 Several other studies have also reported a rash incidence in excess of 40% in patients receiving lapatinib plus a taxane. 5,2326 Although rash is a commonly reported adverse event associated with lapatinib, it appears that the schedule of the coadministered taxane might have an influence on the incidence and severity of this toxicity. In our study, we observed a greater incidence of rash with lapatinib and paclitaxel given every 2 weeks (DD) compared with the reported incidence using the weekly paclitaxel schedule.…”
Section: Discussionmentioning
confidence: 99%